The evaluation of the results in the use of cannabidiol in a child with epileptic seizures (Research, Society and Development, 2023)
Objective: To investigate whether the use of Cannabidiol in children diagnosed with Cerebral Palsy improves motor function and reduces epileptic seizures associated with this pathology. Methodology: This integrative literature review was carried out by collecting data through searches of studies in the databases: National Library of Medicine National Institutes of Health (PubMed) and Virtual Health Library (BVS). Inclusion criteria will consider original articles, published in online databases in the period between 2017 and 2022, in Portuguese, English and Spanish. The descriptors that were used in this study were “Cerebral Palsy” AND “Cannabidiol”, “Cerebral Palsy” AND “Cannabidiol”, “Cannabidiol” AND “Epilepsy” and “Cannabidiol” AND “Epilepsia”. Results: 13 articles were selected, in which it is possible to show that the use of cannabidiol for the treatment of seizures and motor symptoms in children brings benefits such as the reduction in the frequency of seizures. The results of scientific studies obtained so far on the use of CBD in clinical applications may represent hope for patients who are resistant to all conventional antiepileptic drugs. Conclusion: There is still a scarcity of published data, thus preventing the full recommendation of its use for medicinal purposes in pediatrics in cases of epilepsy.